PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PROBLEM BASED LEARNING DENGAN PERMAINAN PLUCKING STAR UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS IX SMP N 1 PATUK GUNUNGKIDUL - SIWI KHOMSIATUN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to improve learning motivation and mathematical problem solving abilities of class IX students of SMPN 1 Patuk Gunungkidul in 2018 on the material of sequences and series of numbers and their use in problem solving. This research is a Classroom Action Research by adopting the model from Kemmis and Tagart which consists of several stages, namely: 1) planning, 2) action, 3) observation, and 4) reflection. The research subjects were students of class IXB SMP N 1 Patuk with 27 students. The data collection instrument used was a learning motivation questionnaire, a problem-solving ability test, and a model effectiveness questionnaire. The results of this Classroom Action Research show that the Problem Based Learning Model and the Plucking Star game can increase students' motivation to learn mathematics from an average score of 4.34 in the